Handedness in low-birthweight children: Insights in lateralization - Ittyerah, Miriam (Frontiers in Psychology, 2023)
Low birthweight children (n= 96) weighing less than 2.5 kg at birth and normal birthweight children (n=96) from Delhi, India, between the ages of 5 and 12 years were assessed for intelligence with the Ravens Coloured Progressive Matrices (RCPM), their handedness and hand proficiency for unimanual and bimanual performance. The objective was to know if there is a relation between birthweight and the development of handedness. Compared to normal birthweight children (NBW), the low birthweight (LBW) group had lower percentile scores for the RCPM. The LBW children were less lateralized than the NBW children in the hand preference test. Though the LBW children were faster than the NBW for sorting objects with each hand separately, they did not display equal left and right hand skill for sorting unlike the NBW children and were slower in the bimanual envelope task. This indicates a delay in inter hemispheric transfer and the development of the corpus callosum that connects the cerebral hemispheres to enable bimanual coordination. In the absence of more direct evidence, hand skill was used as an index of the extent of lateralized control for performance. Findings indicate a relation between birth weight and lateralization in children tested for hand preference.